Synthesizing Effective Strategies for IT-Mediated Writing: A Meta-Ethnographic Study - Fahrus Zaman Fadhly (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2021)
This meta-ethnographic study aims to synthesize effective strategies for IT-mediated writing learning by examining the existing literature on the topic. The study adopts a systematic search and selection process, which results in the inclusion of 20 studies that met the pre-determined inclusion criteria. The findings reveal six overarching themes that represent effective strategies for IT-mediated writing learning, which include (1) collaborative learning, (2) scaffolding, (3) feedback, (4) learner autonomy, (5) multimodal approaches, and (6) contextualization. These themes offer insights into how IT can be used effectively to enhance writing learning in educational settings, particularly in the context of EFL learning. The study concludes by discussing the implications of these findings for both research and practice, and highlighting the need for further research in this area.